ANTIBACTERIAL ACTIVITY AS INHIBITORS PATHOGEN BACTERIAL ON POND SHRIMP OF EXTRACT MARINE BIOTA COLLECTED FROM MASPARI ISLAND, SOUTH SUMATERA, INDONESIA - . Rozirwan; Iskhaq Iskandar; Muhammad Hendri; Rezi Apri; Nuril Azhar (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2018)
Marine biota has variety of bioactive compound that is potential to be an antibacterial for shrimp ponds diseases. Some of marine biota has potential as antibacterial i.e. soft coral Sarcophyton sp., Sponge Aaptos sp., seaweeds Sargassum sp. and Halimeda sp. and mangroves Avicennia sp. and Rhizophora sp. species. This study is purposed to find the most potential marine biota as antibacterial. The research method was as follows; sampling, sample identification, extraction and antibacterial activity test. The results is soft coral and sponge extract Sarcophyton sp. has bioactivity against of shrimp bacteria pathogen such as Vibrio spp2. bacteria for around 6.3±0.1 mm, while Aaptos sp. has bioactivity against Vibrio spp1. bacteria for around 7.9+0.1 mm, Vibrio spp2. bacteria for around 7.2± 0.1 to 7.9±0.1 mm, Vibrio spp6. bacteria for around 7.5±0.2 mm, Escherichia coli for around 7.2±0.1 mm and Staphylococcus aureus for around 15.9±0.2 mm. Seaweed extract activity found only of Sargassum sp. which has antibacterial activity against for around 7.1±0.0 mm for Vibrio spp6. and mangrove species activity has Rhizophora sp. extract which has bioactivity against Vibrio spp4. were 7.3±0.1 mm and E. coli bacteria were 6.7±0.1 mm. The most potential marine biota as antibacterial is showed on sponge Aaptos sp.. with an inhibitory zone for around 15.9±0.2 mm (for S. aureus bacteria).